2022-RA-205-ESGO Circulating HPV DNA in cervical cancer: a marker for early detection of relapse. (20th October 2022) - Jeannot, Emmanuelle; Latouche, Aurélien; Bonneau, Claire; Bataillon, Guillaume; Chérif, Linda Larbi; Popovic, Marina; Rochefordière, Anne de la; Lecuru, Fabrice; Fourchotte, Virginie; Jordanova, Ekaterina; Leyen, Heiko von der; Tran-Perennou, Carine; et al.
Abstract : Introduction/Background: Almost all cervical cancers (CC) are caused by human papillomavirus (HPV) and patients with advanced stage are at high risk for relapse. Studies has shown that most patients with HPV-associated tumors have detectable circulating HPV DNA (HPV ctDNA) in the blood at time of diagnosis, before treatment. Development in sensitive technologies led to the use of cell-free DNA for monitoring patients. In the present study, we investigated if HPV ctDNA may serve as a residual tumor marker at the end of chemo-radiation or to predict relapse during the follow-up period. Methodology: We analyzed serum samples from 94 HPV16- or HPV18-related CCs from the BioRAIDs (NCT02428842 ) prospective cohort. Samples were collected before and after treatment and during an 18-month follow-up period. Using digital droplet PCR (ddPCR), we assessed the relevance of circulating HPV E7 gene as a marker for residual disease. Finally, the prognostic impact of circulating HPV E7 gene was assessed with its prediction value of relapse. Results: Circulating HPV DNA (HPV ctDNA) was detected in 63% (59/94) of patients, before treatment. HPV ctDNA detection in serum sample was associated with high FIGO stage (p=0.02) and para-aortic lymph node involvement (p=0.01). The level of HPV ctDNA was positively correlated with HPV copy number in the tumor (R=0.39, p<0.001). Complete clearance of HPV ctDNA by the end of treatment was significantly associated with a longer PFS (p<0.0001). Patients with persistent HPV ctDNA in serum relapsed with a median time of 10 months (range, 2–15) from HPV ctDNA detection. Conclusion: HPV ctDNA detection is a useful marker to predict relapse in cervical cancer.